Problem-Based Learning (PBL) linked to initial and continuing education for chemistry teachers (Research, Society and Development, 2020)
Problem-Based Learning (PBL) is a methodology that seeks to work on concepts and knowledge in a non-linear and contextualized way. It involves students in an active process of reflection and construction of their own knowledge, contributing to decision making, alone or in groups, and problem solving. It is believed that PBL acts as a strategy aimed at the student, placing him as the protagonist of his learning, and the teacher as a mediator will allow the development of the contents, and enabling him to develop his intellectual autonomy and critical thinking, and in view of these perspectives, the objective of this study was to investigate the participants' conceptions of a short course on the ABP methodology, verifying its applicability in pedagogical practices linked to the teaching of chemistry. The subjects of this study were eight participants, belonging to the area of Natural Sciences and its Technologies and the area of Exact Sciences, in which they participated in a mini-course entitled “Teaching Chemistry through Problem-Based Learning (PBL) in a Context Thematic”. The mini-course provided participants with a space for dialogue and the establishment of new knowledge about PBL. Thus, the subjects involved reported that the methodology can assist in pedagogical practice, and collaborate with Teaching-Learning, shaping the knowledge, knowledge and experiences, which will serve as support when using the methodology in praxis.